Quality Assurance Results for a Commercial Radiosurgery System: A Communication. (October 2015) - Ruschin, Mark; Lightstone, Alexander; Beachey, David; Wronski, Matt; Babic, Steven; Yeboah, Collins; Lee, Young; Soliman, Hany; Sahgal, Arjun
The purpose of this communication is to inform the radiosurgery community of quality assurance (QA) results requiring attention in a commercial FDA-approved linac-based cone stereo-tactic radiosurgery (SRS) system. Standard published QA guidelines as per the American Association of Physics in Medicine (AAPM) were followed during the SRS system's commissioning process including end-to-end testing, cone concentricity testing, image transfer verification, and documentation. Several software and hardware deficiencies that were deemed risky were uncovered during the process and QA processes were put in place to mitigate these risks during clinical practice. In particular, the present work focuses on daily cone concentricity testing and commissioning-related findings associated with the software. Cone concentricity/alignment is measured daily using both optical light field inspection, as well as quantitative radiation field tests with the electronic portal imager. In 10 out of 36 clini-cal treatments, adjustments to the cone position had to be made to align the cone with the collimator axis to less than 0.5 mm and on two occasions the pre-adjustment measured offset was 1.0 mm. Software-related errors discovered during commissioning included incorrect transfer of the isocentre in DICOM coordinates, improper handling of non-axial image sets, and complex handling of beam data, especially for multi-target treatments. QA processes were established to mitigate the occurrence of the software errors. With proper QA processes, the reported SRS system complies with tolerances set out in established guidelines. Discussions with the vendor are ongoing to address some of the hardware issues related to cone alignment.